EUV-permeable film, method for using same, and exposure method

By covering a temporary protective layer that can be removed by EUV exposure on the core material surface of the protective film, the problem of reducing EUV transmittance caused by natural oxide film and side reaction film is solved, and high EUV transmittance during exposure is achieved.

CN119895329APending Publication Date: 2025-04-25NGK INSULATORS LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280007488.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The natural oxide film or side reaction film formed in the atmosphere of the existing protective film causes a decrease in EUV transmittance, and the conventional reaction inhibition protective layer has performance losses in EUV transmittance.

Method used

A main layer with a high EUV transmittance is used, and a temporary protective layer that can be removed by EUV exposure is covered with a surface of the surface. The protective layer includes materials such as amorphous carbon, Cu, Al, and organic resist.

Benefits of technology

Effectively prevent the formation of natural oxide film and side reaction film, avoid the reduction of EUV transmittance, and at the same time, the high transmittance of the main layer is maintained by removing the protective layer during the exposure process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895329A_ABST
    Figure CN119895329A_ABST
Patent Text Reader

Abstract

Provided is an EUV-permeable film which is capable of suppressing the absorption of EUV by a protective layer, which is the main cause of a decrease in EUV transmittance, and which is capable of exhibiting a high EUV transmittance when exposed to light. The EUV-permeable film is provided with: a main layer (12) which has an EUV transmittance of 85% or more at a wavelength of 13.5 nm and which is composed of a single layer or a composite layer of two or more layers; and a protective layer (14) that covers at least one surface of the main layer and contains, as a main component, at least one selected from the group consisting of amorphous carbon, Cu, Al, and an organic resist.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an EUV transparent film, a method of using the film, and an exposure method. Background Art

[0002] The miniaturization of semiconductor manufacturing processes is advancing year by year, and various improvements are being made to each process. In particular, in the photolithography process, EUV (extreme ultraviolet) light with a wavelength of 13.5nm has begun to be used instead of the conventional ArF exposure wavelength of 193nm. As a result, the wavelength suddenly becomes less than 1 / 10, and its optical properties are completely different. However, there is no material with high transmittance for EUV light, so there is no practical component, such as a protective piece (pellicle) as a particle adhesion prevention film for a photomask (reticle). Therefore, device manufacturers currently manufacture semiconductor devices without using protective pieces.

[0003] Therefore, the development of protective membranes is carried out, and the core material of the protective membrane is preferably Si, Be, Y, Zr, etc. with high EUV transmittance. Patent document 1 (Japanese Patent No. 6858817) discloses a protective membrane, which includes: a core layer, which includes a material such as (Poly) Si that is substantially transparent to EUV radiation; and an upper cladding layer, which includes a material that absorbs IR radiation.

[0004] In addition, Patent Document 2 (Japanese Patent Publication No. 2020-98227) discloses a protective film that is stretched and arranged on one end face of a protective frame, and has a main layer of single-crystal Si, and graphene on one or both sides of the main layer. Since the main layer has graphene, the protective film will not be damaged during the manufacture of the protective part, and sufficient mechanical strength can be demonstrated.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 6858817

[0008] Patent Document 2: Japanese Patent Application Publication No. 2020-98227 Summary of the invention

[0009] However, the core material with high EUV transmittance used in the protective film will form a natural oxide film of several nm on its surface in the atmosphere. This oxide film absorbs EUV, resulting in a decrease in the EUV transmittance of the protective film. In particular, Be is a material with high EUV transmittance, but a natural oxide film of 2 to 3 nm will be formed on its surface, and the transmittance loss caused by the oxide film is as high as 6 to 9%. In addition, in the process of making the protective film, sometimes treatment with gases such as fluorine or chlorine other than the atmosphere, acid solutions or alkaline solutions is used, so side reaction films may also be formed on the surface of the core material, resulting in a decrease in EUV transmittance. Therefore, it is desirable to form a protective layer on the surface of the core material to inhibit the formation of these films.

[0010] However, by providing a reaction-inhibiting protective layer on the surface of a core material such as Si or Be, it is possible to prevent the EUV transmittance of the protective film from being significantly reduced. However, such a protective layer has a lower EUV transmittance than the pure core material, resulting in a reduction in the EUV transmittance of the protective film as a whole. For example, Ru can be cited as a protective layer for the Be core material. However, considering that a protective film having a three-layer structure (Ru / Be / Ru) obtained by providing 1 to 2 nm of Ru on the surface and back of the Be core material will have an EUV transmittance loss of approximately 3 to 6% due to the Ru protective layer, the performance of the protective film is significantly reduced. In addition, Si can be cited as a protective layer. 3 N 4 、Be 3 N 2 Such nitrides, however, have the same problem as above, that the EUV transmittance is reduced. That is, an EUV transmitting film is desired that can suppress or eliminate the absorption of EUV by the protective layer, which is the main cause of the reduction in EUV transmittance in conventional pellicles.

[0011] The inventors of the present invention have recently come to the understanding that, by covering a main layer with high EUV transmittance with a temporary protective layer that can be removed by EUV exposure, it is possible to provide an EUV transparent film that can eliminate the absorption of EUV by the protective layer, which is the main cause of the reduction in EUV transmittance, thereby showing a higher EUV transmittance during exposure.

[0012] Therefore, an object of the present invention is to provide an EUV transparent film which can eliminate the absorption of EUV by the protective layer which is the main cause of the decrease in EUV transmittance and can exhibit a high EUV transmittance during exposure.

[0013] According to the present invention, the following solutions are provided.

[0014] [Solution 1]

[0015] An EUV transparent film, comprising:

[0016] A main layer having an EUV transmittance of 85% or more at a wavelength of 13.5 nm and consisting of a single layer or a composite layer of two or more layers; and

[0017] A protective layer covers at least one surface of the main layer and contains at least one selected from the group consisting of amorphous carbon, Cu, Al, and an organic resist as a main component.

[0018] [Solution 2]

[0019] The EUV transparent film according to claim 1, wherein

[0020] Both sides of the main layer are covered by the protective layer.

[0021] [Solution 3]

[0022] The EUV transparent film according to claim 1 or 2, wherein

[0023] The main layer contains Be, Si, Y or Zr as a main component.

[0024] [Solution 4]

[0025] The EUV transparent film according to any one of items 1 to 3, wherein

[0026] The thickness of the protective layer is less than 5 nm.

[0027] [Solution 5]

[0028] The EUV transparent film according to any one of items 1 to 4, wherein

[0029] The protective layer is composed of amorphous carbon.

[0030] [Solution 6]

[0031] A method for using an EUV transparent film, comprising:

[0032] A step of installing the EUV transparent film according to any one of items 1 to 5 in an EUV exposure device, and

[0033] a step of irradiating the EUV transparent film with EUV to remove the protective layer.

[0034] [Solution 7]

[0035] An exposure method, comprising:

[0036] A step of installing the EUV transparent film according to any one of items 1 to 5 in an EUV exposure device,

[0037] a step of irradiating the EUV transparent film with EUV to remove the protective layer and expose the main layer; and

[0038] A step of allowing EUV to pass through the main layer exposed by EUV irradiation and performing pattern exposure on the photosensitive substrate in the EUV exposure device. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic cross-sectional view showing one form of the EUV transmitting film of the present invention.

[0040] Figure 2A This is a process flow chart showing the first half of the steps for manufacturing the EUV transparent film in Examples 1 to 3.

[0041] Figure 2B This is a process flow chart showing the second half of the manufacturing steps of the EUV transparent film in Examples 1 to 3. DETAILED DESCRIPTION

[0042] EUV transparent film

[0043] Figure 1 , a simplified cross-sectional view of an EUV transparent film 10 according to one embodiment of the present invention is shown. The EUV transparent film 10 comprises: a main layer 12, and a protective layer 14 covering at least one side of the main layer 12. The EUV transmittance of the main layer 12 at a wavelength of 13.5 nm is 85% or more, and is composed of a single layer or a composite layer of two or more layers. The protective layer 14 contains at least one selected from the group consisting of amorphous carbon, Cu, Al and an organic resist as a main component. By covering the main layer with a high EUV transmittance with a temporary protective layer that can be removed by EUV exposure in this way, it is possible to provide an EUV transparent film that can eliminate the absorption of EUV by the protective layer, which is the main cause of the reduction in EUV transmittance, and can thereby exhibit a high EUV transmittance during exposure.

[0044] As described above, a core material with a high EUV transmittance sometimes forms a natural oxide film of several nm on its surface in the atmosphere. In addition, in the process of making the protective film, treatment with gases such as fluorine or chlorine other than the atmosphere, an acid solution or an alkaline solution is sometimes used, so a side reaction film is sometimes formed on the surface of the core material. Due to the formation of such a film, the EUV transmittance of the protective film is reduced. Therefore, it is expected to form a protective layer on the surface of the core material to inhibit the formation of these films. However, by providing a reaction-inhibiting protective layer on the surface of the core material, the EUV transmittance of the protective film as a whole is reduced. According to the EUV transparent film of the present invention, these problems are solved smoothly. The mechanism by which the EUV transparent film of the present invention can prevent the formation of natural oxide films and the like and can prevent the reduction of EUV transmittance caused by the protective layer is as follows. The EUV transparent film of the present invention comprises: a main layer with a high EUV transmittance, and a protective layer covering at least one side of the main layer, the protective layer being a temporary protective layer that can be removed by EUV exposure. That is, the protective film will form the above-mentioned natural oxide film or side reaction film during the exposure process when it is manufactured and mounted on the EUV exposure device, and the EUV transparent film of the present invention can prevent the formation of the above-mentioned film by having a protective layer. Next, the exposure process is usually carried out in a hydrogen atmosphere, in which there are many hydrogen radicals generated by EUV. Therefore, by forming the protective layer with a material that can be removed by hydrogen radicals, the protective film of the EUV transparent film in the exposure device is removed, and a film with only pure core material (main layer) is obtained, so that as a protective film, a higher transmittance can be reflected. According to such a mechanism, the EUV transparent film of the present invention can prevent the formation of natural oxide film, etc. by using a temporary protective layer, and can prevent the reduction of EUV transmittance caused by the protective layer by removing the temporary protective layer in the exposure process. As a result, a higher EUV transmittance can be reflected during exposure.

[0045] The EUV transmittance of the main layer 12 at a wavelength of 13.5 nm is 85% or more, preferably 92% or more, more preferably 94% or more, and further preferably 96% or more. During the exposure process, the protective layer 14 in the EUV transparent film 10 is removed, and the main layer 12 remains. Therefore, the higher the EUV transmittance of the main layer 12, the better. The upper limit is not particularly limited, and is ideally 100%. However, it is typically 99% or less, and more typically 98% or less.

[0046] The main layer 12 can be a single layer or a composite layer of two or more layers. In any case, the main layer 12 preferably contains Be, Si, Y or Zr as the main component. Here, the "main component" in the main layer 12 refers to: a component that occupies more than 50 mol%, preferably more than 70 mol%, more preferably more than 80 mol%, and further preferably more than 90 mol% of the main layer 12. However, the main layer 12 (especially a single layer or at least one layer constituting a composite layer) can be composed only of Be, Si, Y or Zr. Such a main layer 12 can ensure the basic functions as a protective film (such as the function of preventing particle adhesion), and contribute to the realization of a higher EUV transmittance. From the above viewpoint, the thickness of the main layer 12 is preferably 10 to 70 nm, more preferably 15 to 50 nm, and further preferably 20 to 35 nm.

[0047] As described above, the main layer 12 may be a composite layer of more than two layers. For example, if a protective layer of amorphous carbon is directly provided on the metal beryllium layer, i.e., the main layer, sometimes the amorphous carbon and the metal beryllium react to form beryllium carbide. Therefore, for example, by providing the main layer 12 with a composite layer structure such as a metal beryllium layer / beryllium nitride layer (or a beryllium nitride layer / metal beryllium layer / beryllium nitride layer), and providing a protective layer of amorphous carbon on the beryllium nitride layer, the reaction between the amorphous carbon and the metal beryllium can be prevented, that is, the reaction between the main layer and the protective layer can be suppressed. It should be noted that the term "beryllium nitride" in this specification refers not only to Be 3 N 2 Such a stoichiometric composition also allows Be 3 N 2-x (wherein 0<x<2) is a generalized composition of such non-stoichiometric composition.

[0048] The protective layer 14 is a layer used to temporarily protect the main layer 12. Therefore, the protective layer 14 only needs to cover at least one side of the main layer 12, but it is preferred to cover both sides of the main layer 12 with the protective layer. The protective layer 14 contains at least one selected from the group consisting of amorphous carbon, Cu, Al and organic resist as a main component. Considering the high EUV transmittance, the small impact of the residue on the main layer 12 when the protective layer 14 is removed, and the easy removal of the protective layer 14, the protective layer 14 preferably contains amorphous carbon as a main component, and more preferably is composed of amorphous carbon. Generally, amorphous carbon rarely has a completely irregular atomic arrangement, and has a crystalline structure (i.e., has microcrystals) microscopically. At this time, such irregular arrangement of microcrystals makes the whole amorphous in most cases. Among them, a substance containing many three-dimensional 4-coordinate structure microcrystals like diamond is called DLC (Diamond-like Carbon), and a substance containing many planar 3-coordinate structure particles like graphite is called GLC (Graphite-like Carbon). The protective layer 14 can be carbon with a completely irregular atomic arrangement, or carbon with irregular microcrystals. In addition, it can also be amorphous carbon containing fine pores but not completely dense. Here, the "main component" in the protective layer 14 refers to: a component that occupies a weight of more than 50% by weight, preferably more than 60% by weight, more preferably more than 70% by weight, and further preferably more than 80% by weight in the total weight of the protective layer 14. However, the protective layer 14 can be composed of only at least one selected from the group consisting of amorphous carbon, Cu, Al and organic resist.

[0049] The thickness of the protective layer 14 is preferably 5 nm or less, and more preferably 3 nm or less. The lower limit of the thickness of the protective layer 14 is not particularly limited, but is typically 1 nm or more.

[0050] As described above, the main layer 12 may be a composite layer of two or more layers. For example, the main layer 12 may include a nitride layer such as a beryllium layer on one or both sides in addition to a metal layer such as a beryllium layer. In this case, the main layer 12 preferably has a nitrogen concentration gradient region in which the nitrogen concentration decreases as it approaches the metal layer such as the beryllium layer. That is, the composition of beryllium nitride may include Be nitride. 3 N 2 Such a stoichiometric composition to Be 3 N 2-x(where 0<x<2) is a non-stoichiometric composition. In this case, the beryllium nitride constituting the beryllium nitride layer is preferably a gradient composition whose composition approaches the beryllium-rich composition as it approaches the beryllium layer. Accordingly, the adhesion between the nitride layer (i.e., the beryllium nitride layer) and the metal layer (i.e., the beryllium layer) constituting the main layer 12 can be improved, and the stress caused by the thermal expansion difference between the two layers can be alleviated. That is, the adhesion between the two layers can be improved to suppress peeling, or the two layers can be made less likely to peel off as a thermal expansion mitigation layer between the two layers when EUV light is absorbed and the temperature reaches a high temperature. The thickness of the nitrogen concentration gradient region is preferably less than the thickness of the nitride layer. That is, the entire region without the thickness of the nitride layer is the nitrogen concentration gradient region. For example, it is preferred that only a portion of the thickness of the nitride layer, such as a region preferably 10 to 70% of the thickness of the nitride layer, is the nitrogen concentration gradient region, and more preferably a region 15 to 50% is the nitrogen concentration gradient region.

[0051] The EUV transparent film 10 is preferably in the form of a self-supporting film in the main area for EUV transmission. That is, it is preferred that only the outer edge of the EUV transparent film 10 has a substrate (such as a Si substrate) used during film formation remaining in the form of a border, that is, it is preferred that no substrate (such as a Si substrate) remains in the main area other than the outer edge, that is, the main area is composed only of the main layer 12 and the protective layer 14. In addition, it is preferred that the protective layer 14 is completely removed during the exposure process. It should be noted that the exposure device is usually depressurized to an ultra-high vacuum before processing begins. Therefore, the oxygen partial pressure inside the exposure device is significantly lower, and the main layer 12 exposed by the removal of the protective layer 14 is almost not oxidized. Although the surface of the main layer 12 may be very slightly oxidized due to a small amount of residual oxygen in the exposure device, the oxidized portion can be reduced by EUV irradiation in a hydrogen atmosphere. Therefore, the EUV transparent film 10 used in the exposure process can maintain a high EUV transmittance before being taken out of the exposure device.

[0052] Manufacturing method

[0053] The EUV transparent film of the present invention can be produced by forming a laminated film to be made into an EUV transparent film on a Si substrate, and then removing unnecessary parts of the Si substrate by etching to form a self-standing film, thereby producing the EUV transparent film. Therefore, as described above, the main part of the EUV transparent film is in the form of a self-standing film without any remaining Si substrate.

[0054] (1) Preparation of Si substrate

[0055] First, a Si substrate for forming a laminated film thereon is prepared. After a laminated film including a main layer 12 and a protective layer 14 is formed on the Si substrate, the main area (i.e., the area to be made into a self-supporting film) excluding the outer edge is removed by etching. Therefore, in order to perform etching efficiently in a short time, it is preferred to thin the thickness of the Si substrate in the area to be made into a self-supporting film in advance. Therefore, it is desirable to form a mask corresponding to the EUV transmission shape on the Si substrate using a conventional semiconductor process, and to etch the Si substrate using wet etching so that the thickness of the main area of ​​the Si substrate is thinned to a specified thickness. The wet-etched Si substrate is cleaned and dried, thereby preparing a Si substrate having a cavity formed by wet etching. It should be noted that as a wet etching mask, any material that is resistant to corrosion by a wet etching solution for Si can be used. For example, SiO 2 In addition, the wet etching liquid is not particularly limited as long as it can etch Si. For example, if TMAH (tetramethylammonium hydroxide) is used under appropriate conditions, it can etch Si very well with anisotropic etching, so it is preferred.

[0056] (2) Formation of laminated films

[0057] The formation of the laminated film can be carried out by any film forming method. As an example of a preferred film forming method, sputtering can be cited. In the case of making a three-layer structure of amorphous carbon / beryllium / amorphous carbon, it is preferred to use sputtering using a pure Be target to make a beryllium film as the main layer 12, and to use sputtering using a graphite target to make an amorphous carbon film as the protective layer 14. It should be noted that the method for forming the beryllium film and the amorphous carbon film is not limited to these methods. In addition, the beryllium film and the amorphous carbon film can be formed in a sputtering device in one chamber as in the embodiment described later, or a sputtering device in two chambers can be used to form the beryllium film and the amorphous carbon film in each chamber.

[0058] When the main layer 12 is made into a composite layer of a three-layer structure of beryllium nitride / beryllium / beryllium nitride, it is preferred to use sputtering using a pure Be target to make the beryllium film, and to use reactive sputtering to make the beryllium nitride film. The reactive sputtering can be performed as follows. For example, in sputtering using a pure Be target, nitrogen gas is introduced into the chamber, whereby beryllium and nitrogen react to form beryllium nitride. In addition, as another method, the production of beryllium nitride can also be performed as follows, that is, after forming the beryllium film, nitrogen plasma is irradiated, whereby beryllium undergoes a nitridation reaction to form beryllium nitride. In short, the synthesis method of beryllium nitride is not limited to these methods.

[0059] In the case of forming a nitrogen concentration gradient region in a composite layer of a three-layer structure of beryllium nitride / beryllium / beryllium nitride, when forming beryllium nitride and metal beryllium, nitrogen is introduced into the chamber while continuing sputtering using a pure Be target, and the introduction of nitrogen is stopped midway and switched to forming metal beryllium. Accordingly, as the concentration of nitrogen in the chamber decreases, a region is formed in which the nitrogen concentration in the formed film decreases along the thickness direction. On the other hand, in the case of switching from metal beryllium to beryllium nitride, contrary to the above, if sputtering is continued while nitrogen is introduced midway, a nitrogen concentration gradient region can be formed. By adjusting the time for changing the concentration of nitrogen gas, the thickness of the nitrogen concentration gradient region can be controlled.

[0060] (3) Self-supporting membrane

[0061] The unnecessary part of the Si substrate except the outer edge of the Si substrate on which the composite film is formed is removed by etching to form a self-standing composite film. The etching of Si can be performed by any method, preferably by using XeF 2 The etching is carried out.

[0062] How to use and how to expose

[0063] As described above, the exposure process is usually carried out in a hydrogen atmosphere, in which there are many hydrogen radicals generated by EUV. Therefore, the protective layer 14 in the EUV transparent film 10 is removed by hydrogen radicals to obtain a film with only pure core material (main layer 12). Therefore, in the exposure process, the main layer 12 can act as a protective film and exhibit a higher transmittance. Therefore, the preferred method of using the EUV transparent film includes: a process of installing the EUV transparent film in an EUV exposure device, and a process of irradiating EUV to the EUV transparent film to remove the protective layer. In addition, the preferred exposure method includes: a process of installing the EUV transparent film in an EUV exposure device, a process of irradiating EUV to the EUV transparent film to remove the protective layer and expose the main layer, and a process of allowing EUV to pass through the main layer exposed by EUV irradiation and performing pattern exposure on the photosensitive substrate in the EUV exposure device.

[0064] Example

[0065] The present invention will be further specifically described by the following examples.

[0066] Example 1

[0067] according to Figure 2A and Figure 2B The steps shown are as follows to prepare a composite self-supporting film (EUV transmitting film) having a three-layer structure of amorphous carbon / beryllium / amorphous carbon.

[0068] (1) Preparation of Si substrate

[0069] Prepare a Si wafer 20 (8 inches (20.32 cm) in diameter) Figure 2A (a)) On both sides of the Si wafer 20, SiO2 is formed with a thickness of 50 nm by thermal oxidation. 2 Membrane 22( Figure 2A (b)) A resist was applied to both sides of the Si wafer 20, and exposure and development were performed so that a resist hole of 110 mm×145 mm could be formed on one side to form a SiO 2 The resist mask 24 for etching ( Figure 2A (c)). One surface of the substrate is wet-etched with hydrofluoric acid to remove SiO 2 The exposed portion of the film 22 is removed by etching to form SiO 2 Mask 22a( Figure 2A (d)). SiO 2 The resist mask 24 for etching is removed by an ashing device ( Figure 2A (e)). Then, the Si is wet-etched using TMAH solution. The etching rate is measured in advance, and the etching time is set to the target Si substrate thickness of 50 μm. ( Figure 2A (f)). Finally, the SiO formed on the surface where Si etching was not performed 2 The film 22 is removed and cleaned by hydrofluoric acid, and a Si substrate 28 ( Figure 2B (g)). Regarding the shape of the Si substrate, it can be cut using laser 30 as needed ( Figure 2B (h)), set to the desired shape ( Figure 2B (i)) In this way, a Si substrate 28 was prepared in which a cavity 26 of 110 mm×145 mm was provided in the center of an 8-inch (20.32 cm) Si wafer 20 and the Si thickness of the cavity 26 portion was 50 μm.

[0070] (2) Formation of composite membrane

[0071] The Si substrate 28 having the cavity 26 obtained in the above (1) is formed into a composite film having a three-layer structure of amorphous carbon / beryllium / amorphous carbon as follows ( Figure 2B(i)). First, the Si substrate 28 is fixed to a multi-target sputtering device, and a graphite target and a pure Be target are installed. The chamber is evacuated, and a graphite target is used with an internal pressure of 0.3 Pa. Sputtering is performed only with argon gas, and the DLC (Diamond-like Carbon) film, which is amorphous carbon, is formed to a thickness of 2 nm, and the sputtering is terminated. Next, the chamber is evacuated again, and a pure Be target is used with an internal pressure of 0.5 Pa. Sputtering is performed only with argon gas, and the sputtering is terminated when the beryllium film is formed to a thickness of 30 nm. Thereafter, sputtering is performed using a graphite target in the same manner as at the beginning, and the sputtering is terminated when the amorphous carbon film is formed to a thickness of 2 nm. In this way, a composite film of amorphous carbon (C) 2 nm / beryllium (Be) 30 nm / amorphous carbon (C) 2 nm is formed as an EUV transparent film 10. That is, the EUV transparent film 10 comprises a main layer containing Be as a main component, and protective layers containing amorphous carbon as a main component are provided on both sides of the main layer.

[0072] (3) Self-supporting membrane

[0073] In XeF, which can process 8-inch (20.32 cm) substrates 2 The Si substrate 28 with the composite film prepared in (2) is fixed in the chamber of the electroetcher. The chamber is fully evacuated. At this time, if there is any water left in the chamber, it will be mixed with XeF 2 The gases react to produce hydrofluoric acid, which may cause corrosion of the etcher or unexpected etching. Therefore, the chamber should be fully evacuated. If necessary, the chamber should be repeatedly evacuated and nitrogen gas introduced to reduce residual moisture. After the chamber is fully evacuated, turn on the XeF 2 The valve between the raw material bottle and the preparation chamber. As a result, XeF 2 Sublimation, XeF also accumulates in the preparation room 2 XeF is fully accumulated in the preparation room. 2 After the gas is released, open the valve between the preparation chamber and the chamber to release XeF 2 Gas is introduced into the chamber. XeF 2 The gas decomposes into Xe and F, and F reacts with Si to form SiF 4 。SiF 4 The boiling point of SiF is -95°C. 4 Rapid evaporation, the newly exposed Si substrate reacts with F. After Si etching, the F in the chamber is reduced, the chamber is evacuated and XeF is added again. 2 Gas is introduced into the chamber to perform etching. This process of vacuuming, XeF 2Gas is introduced and etching is continued until the Si substrate 28 corresponding to the self-supporting film portion disappears. After the unnecessary portion of the Si substrate disappears, the etching is terminated. In this way, a composite self-supporting film having a Si border 20 is obtained as an EUV transparent film 10 ( Figure 2B (j)).

[0074] Example 2 (Comparison)

[0075] A composite self-supporting film having a three-layer structure of ruthenium / beryllium / ruthenium was prepared in the same manner as in Example 1 except that the composite film was formed as follows.

[0076] (Formation of composite film)

[0077] The Si substrate with a cavity formed therein obtained in (1) of Example 1 is placed in a multi-target sputtering device, and a pure ruthenium target and a pure Be target are installed. The chamber is evacuated, and a pure ruthenium target is used with an internal pressure of 0.3 Pa. Sputtering is performed only with argon gas, and the sputtering is terminated when the ruthenium film has formed 2 nm. Next, the chamber is evacuated again, and a pure Be target is used with an internal pressure of 0.5 Pa. Sputtering is performed only with argon gas, and the sputtering is terminated when the beryllium film has formed 30 nm. Thereafter, sputtering is performed using a pure ruthenium target in the same manner as in the initial step, and the sputtering is terminated when the ruthenium film has formed 2 nm. In this way, a composite film of ruthenium (Ru) 2nm / beryllium (Be) 30nm / ruthenium (Ru) 2nm is formed as an EUV transparent film.

[0078] Example 3 (Comparison)

[0079] A composite self-supporting film having a three-layer structure of crystalline carbon / beryllium / crystalline carbon was prepared in the same manner as in Example 1 except that the composite film was formed as follows.

[0080] (Formation of composite film)

[0081] The Si substrate with the cavity formed in (1) of Example 1 is placed in a chemical vapor growth (CVD (Chemical Vaper Deposition)) device, and methane is used as a gas raw material to form a 2nm crystalline carbon film having a crystalline structure of graphite. Next, the Si substrate with the crystalline carbon film formed is placed in a multi-target sputtering device, and a graphite target and a pure Be target are installed. The chamber is evacuated, and a pure Be target is used with an internal pressure of 0.5Pa. Sputtering is performed only with argon gas. When the beryllium film is formed for 30nm, the sputtering is terminated. A graphite target is used with an internal pressure of 0.3Pa. Sputtering is performed only with argon gas. When the amorphous carbon film is formed for 0.5nm, the sputtering is terminated. Thereafter, the sputtered Si substrate is placed in a vapor growth device again, and hydrogen cleaning is performed until the amorphous carbon is fully removed. As in the initial step, methane is used as a gas raw material to form a 2nm crystalline carbon film having a crystalline structure of graphite. Thus, a composite film of crystalline carbon (C) 2nm / beryllium (Be) 30nm / crystalline carbon (C) 2nm was formed as an EUV transmission film. It should be noted that the amorphous carbon temporarily formed by sputtering is formed to suppress beryllium oxidation during the period from sputtering to chemical vapor growth.

[0082] EUV transmittance

[0083] For the self-supporting films as EUV transparent films prepared in Examples 1 to 3, EUV light was irradiated at an output power of 600W for 15 minutes in a hydrogen atmosphere of 20Pa, and then the amount of EUV light that had been transmitted was measured by a sensor. The EUV transmittance was calculated by comparing the measured value obtained with the value obtained by measuring the direct EUV light amount using the sensor in the state without the EUV transparent film. As a result, the EUV transmittance of the composite self-supporting film prepared in Example 1 was 95%. The EUV transmittance of the composite self-supporting film prepared in Example 2 as a comparative example was 88%. The EUV transmittance of the composite self-supporting film prepared in Example 3 as a comparative example was 90%. The composite self-supporting film in Example 3 was analyzed, and it was confirmed that crystalline carbon remained in the protective layer. That is, for the composite self-supporting film of crystalline carbon / beryllium / crystalline carbon in Example 3, it is believed that: in the exposure process, the crystalline carbon is not easily removed and remains on the surface of the main layer of beryllium, resulting in a decrease in the EUV transmittance of the composite self-supporting film. On the other hand, regarding the amorphous carbon / beryllium / amorphous carbon composite self-supporting film of Example 1, it is considered that the amorphous carbon was removed during the exposure process, leaving only the main layer of beryllium, and therefore exhibited a high EUV transmittance of 95%.

Claims

1. An EUV transparent film, wherein: have: A main layer having an EUV transmittance of 85% or more at a wavelength of 13.5 nm and consisting of a single layer or a composite layer of two or more layers; and A protective layer covers at least one surface of the main layer and contains at least one selected from the group consisting of amorphous carbon, Cu, Al, and an organic resist as a main component.

2. The EUV transparent film according to claim 1, wherein: Both sides of the main layer are covered by the protective layer.

3. The EUV transparent film according to claim 1, wherein The main layer contains Be, Si, Y or Zr as a main component.

4. The EUV transparent film according to claim 1 or 2, wherein: The thickness of the protective layer is less than 5 nm.

5. The EUV transparent film according to claim 1 or 2, wherein: The protective layer is composed of amorphous carbon.

6. A method for using an EUV transparent film, wherein: include: A step of installing the EUV transparent film according to claim 1 or 2 in an EUV exposure device, and a step of irradiating the EUV transparent film with EUV to remove the protective layer.

7. An exposure method, wherein: include: A step of installing the EUV transparent film according to claim 1 or 2 in an EUV exposure device, a step of irradiating the EUV transparent film with EUV to remove the protective layer and expose the main layer; and A step of allowing EUV to pass through the main layer exposed by EUV irradiation and performing pattern exposure on the photosensitive substrate in the EUV exposure device.

Citation Information

Patent Citations

  • Pellicle film for photo lithography and pellicle equipped with the same

    JP2020098227A